University of Baghdad/ College of Physical Education & Sport Sciences Students Attitudes towards Drugs - Hameed, Abdalhadi; Maki, Ali; Salam, Karam (Journal of Physical Education, 2020)
The research aims at identifying university of Baghdad/ college of physical education and sport sciences students’ attitudes towards drugs. It also aims at identifying the differences between female and male students during the academic year 2018 – 2019. The research was conducted on a sample of 240 students. The study found positive attitudes for boys and girls towards drug use. There are significant differences in favor of girls. The average value of girls and boys is less than the average value of 110. In the light of the results, the researcher presented a number of recommendations and suggestions, including the need to coordinate universities with men of religion to hold seminars on addiction and encourage them to include their sermons and religious lessons on the role of mind, spirit and self in the formation of an anti-drug trend and encourage all stages of sport (school, university, military, clubs and teams). The family should play an active role. The family represents the first and most prominent line of defense and social immunity. Resistance efforts and control is incomplete and liable to failure if the family is not one of the pillars of these efforts.